An investigation of the five-factor model of personality and coping behaviour in sport - Allen, M. S.; Greenlees, I.; Jones, M. (Journal of Sports Sciences, 2011)
Coping strategies are important for performance in sport and individual differences may contribute to the coping strategies adopted by athletes. In this study, we explored the main and interactive effects of the big five personality dimensions on sport-related coping and compared personality profiles of discrete groups of athletes. Altogether, 253 athletes (mean age 21.1 years, s = 3.7) completed the NEO-FFI (Costa & McCrae, 1992) , and the Coping Function Questionnaire for Sport (Kowalski & Crocker, 2001). Results showed that extraverted athletes, who were also emotionally stable and open to new experiences (a three-way interaction effect), reported a greater use of problem-focused coping strategies. Conscientious athletes (main effect), and athletes displaying high levels of extraversion, openness, and agreeableness (a three-way interaction effect), reported a greater use of emotion-focused coping strategies, and athletes with low levels of openness, or high levels of neuroticism (main effects), reported a greater use of avoidance coping strategies. Different personality characteristics were observed between higher-level and lower-level athletes, between men and women athletes, and between individual and team sport athletes. These findings suggest that the five-factor model of personality can help distinguish various levels of athletic involvement and can help identify the coping strategies athletes are likely to adopt during participation.